Melampaui Kepercayaan Informal: Akuntansi Syariah dan Akuntabilitas Akad Bagi Hasil dalam Kontrak Muzara’ah di Pedesaan Indonesia - Siska Melida Saragih; Yenni Samri Juliati Nasution; Laylan Syafina (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2026)
Muzara’ah-based agricultural partnerships remain common in rural Indonesia, yet they are often arranged orally and lack systematic financial records, reducing transparency and creating ambiguity in cost allocation and profit-sharing. This study analyzes the implementation of sharia accounting principles in muzara'ah practices in Raya Bayu Village, Simalungun Regency, and assesses their fairness, transparency, and accountability. Using a qualitative case study approach, data were collected through observation, semi-structured interviews, and documentation from fifteen informants: seven landowners, seven tenant farmers, and one farmer-group leader. Data were analyzed through reduction, display, and conclusion drawing, supported by triangulation and member checking. The findings show that muzara'ah practices substantively reflect sharia values, especially mutual consent, trust, and fair profit-sharing after deducting production costs. However, accounting practices remain simple, manual, inconsistent, and not equally accessible, so sharia accounting functions more as a value-based ethic than a fully developed procedure and needs simple shared records to strengthen accountability.